2014
DOI: 10.1039/c3bm60289c
|View full text |Cite
|
Sign up to set email alerts
|

A nanopatterned cell-seeded cardiac patch prevents electro-uncoupling and improves the therapeutic efficacy of cardiac repair

Abstract: The heart is an extremely sophisticated organ with nanoscale anisotropic structure, contractility and electro-conductivity; however, few studies have addressed the influence of cardiac anisotropy on cell transplantation for myocardial repair. Here, we hypothesized that a graft's anisotropy of myofiber orientation determines the mechano-electrical characteristics and the therapeutic efficacy. We developed aligned- and random-orientated nanofibrous electrospun patches (aEP and rEP, respectively) with or without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 65 publications
0
31
0
Order By: Relevance
“…It is probably because the benefits of material injection are due to passively providing mechanical support. [35][36][37][38] To truly improve cardiac systolic function and pumping ability, it relies on either directly implanting constructs with actively contractive cells [38][39][40][41] or indirectly reducing loss of host cardiomyocytes by angiogenesis or paracrine effects from biological substance. 42,43 We previously showed angiogenesis was induced by MNC transplantation with/without NFs at 1 month post-MI.…”
Section: Discussionmentioning
confidence: 99%
“…It is probably because the benefits of material injection are due to passively providing mechanical support. [35][36][37][38] To truly improve cardiac systolic function and pumping ability, it relies on either directly implanting constructs with actively contractive cells [38][39][40][41] or indirectly reducing loss of host cardiomyocytes by angiogenesis or paracrine effects from biological substance. 42,43 We previously showed angiogenesis was induced by MNC transplantation with/without NFs at 1 month post-MI.…”
Section: Discussionmentioning
confidence: 99%
“…Burridge et al [54] used AFM to verify that interaction of iPSC-CMs with other cell types in a 3D hydrogel did not interfere with the contractile activity. Lin and co-workers [61] investigated the effect of size and orientation of electro-spun fibrous patches of gelatine-coated polyacrylonitrile on the beating frequency and force of neonatal rat myocytes. Authors found that CMs on aligned nanofibres beat faster and stronger than those on randomly oriented ones.…”
Section: Afm Quantification Of Beating Activitymentioning
confidence: 99%
“…In the present weaving technique, two distinct sets of warps (PAN MY) and wefts (PAN UANY) are interlaced at right angles to form nano-micro fibrous woven fabrics, which can effectively mimic the fiber architecture and physical anisotropy of native ECM of aortic valve leaflet. Although PAN is not a widely-used material, it has been demonstrated by our group and others to be a biocompatible material for both in vitro and in vivo applications [34,56,57]. With the additional capacity for textile processing and cellularization, PAN based scaffolds have unique advantages for fabricating engineered valve conduits.…”
Section: Discussionmentioning
confidence: 99%